A study of difficulties in teaching and learning reading comprehension in the course book “New Headway (Pre-Intermediate) to the first year students at college of Broadcasting 1, Phu Ly city, Ha Nam province and some solutions - Nguyen, Thi Lan Huong (University of Languages and International Studies, 2017)
This minor thesis was carried out with an attempt to investigate the current difficulties the teachers and the first year students are coping with in teaching and learning Reading comprehension in the course book New Headway" (Pre-Intermediate) in the col (...)"